Metastasis of Papillary Thyroid Carcinoma to the Maxillary Sinus: Case Report and Review of the Literature - Hajime Shimmura; Eri Mori; Rumi Sekine; Masayoshi Tei; Nobuyoshi Otori (Case Reports in Otolaryngology)
Metastasis of the thyroid carcinoma to the paranasal sinuses is rarely reported. Among these sinuses, metastasis to the maxillary sinus alone has been reported only in a few cases. This is the first reported case in a 76-year-old woman with papillary thyroid carcinoma metastasizing to the maxillary sinus alone and resected through endoscopic sinonasal surgery. When patients have sinus lesions and a history of malignancy, metastasis should be included in the differential diagnosis. If they have an isolated metastatic lesion to the paranasal sinus, ESS, either palliative or radical, can be a useful treatment option.